2020
DOI: 10.1613/jair.1.12225
|View full text |Cite
|
Sign up to set email alerts
|

To Regulate or Not: A Social Dynamics Analysis of an Idealised AI Race

Abstract: Rapid technological advancements in Artificial Intelligence (AI), as well as the growing deployment of intelligent technologies in new application domains, have generated serious anxiety and a fear of missing out among different stake-holders, fostering a racing narrative. Whether real or not, the belief in such a race for domain supremacy through AI, can make it real simply from its consequences, as put forward by the Thomas theorem. These consequences may be negative, as racing for technological supremacy cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(96 citation statements)
references
References 44 publications
2
94
0
Order By: Relevance
“…Let us depart from the innovation race or domain supremacy through AI race (DSAIR) model developed in [ 13 ]. We adopt a two-player repeated game, consisting of, on average, W rounds.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Let us depart from the innovation race or domain supremacy through AI race (DSAIR) model developed in [ 13 ]. We adopt a two-player repeated game, consisting of, on average, W rounds.…”
Section: Methodsmentioning
confidence: 99%
“…When a SAFE player interacts with an UNSAFE player, the SAFE one pays a cost c and receives a (smaller) part b /( s + 1) of the benefit b , while the UNSAFE one obtains the larger part sb /( s + 1) without having to pay c . Note that Π is a simplification of the matrix defined in [ 13 ] since it was shown that the parameters defined here are sufficient to explain the results in the current time-scale.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations